Assessing comparative advantage of Pakistan with United States of America: the role of Pakistan’s export financial sector - Sultan, Khurram; Zainal Abidin, Irwan Shah (2017)
Present study endeavors to assess the comparative advantage of Pakistan’s exports to United Sates of America. Generally comparative advantage is an important concept for explaining pattern of international trade. Aim of the study is to check out that in how many product categories Pakistan has RCA and from these how many able to export to USA. Revealed Comparative Advantage Balassa Index (1965) over the sample of 961 Product categories have been taken with the time Spain 2001-2016. Data took from the website of Un-Com Trade. Results revealed that Pakistan has a comparative advantage in 29 product categories and from these 29 products Pakistan able to export 26 products to United States of America because United States of America has comparative disadvantage in these 26 product categories.